Classroom activities as predictors of control, value, and state emotions in science. Issue 6 (2nd November 2021) - Beymer, Patrick N.; Robinson, Kristy A.; Schmidt, Jennifer A.
Abstract: This article examined relations among classroom activities, students' momentary control- and value-related appraisals, and students' state emotions in high school science classrooms. Throughout 10 days of instruction, high school students ( N = 244) reported their state emotions and task-specific control- and value-related appraisals during science class, while classroom activities were observed via video. Results obtained through structural equation modeling and MANOVA suggest that perceived value, control, and emotions differed significantly across classroom activities. Classroom activities exhibited direct effects on emotions as well as indirect effects via control and value appraisals. Results suggest that theorized links among environment, appraisals, and emotions may differ by both the emotion and the classroom activity under consideration.